The Effects of Religious Orientations on Malevolent Creativity: Role of Positive Emotions and Spiritual Intelligence. Issue 4 (1st October 2020) - khorakian, Alireza; Hemsworth, David; Jahangir, Mostafa; Maharati, Yaghoob; Bagherpour, Elahe Sadat; Muterera, Jonathan
ABSTRACT: Creativity has long been touted as one of the aspects of human behavior that truly delineates mankind from all other species. However, sometimes people use creativity in negative ways, whereby it is used to reach goals through harming others. Often these malevolent acts are sensationalized in the media. Previous research found that there is a relationship between malevolent creativity and religious beliefs. This research evaluates the effect of two dimensions of religious orientation, intrinsic and extrinsic, on malevolent creativity through the mediating roles of positive emotions and spiritual intelligence. Data were collected from 862 Muslim students from the countries of Iran, Iraq, Yemen, Afghanistan and Syria. In this research, intrinsic religious orientation was found to reduce students' malevolent creativity while extrinsic religious orientation increased the malevolent creativity. Furthermore, the effect of intrinsic religious orientation on malevolent creativity through spiritual intelligence and positive emotion was negative, whereas this effect for extrinsic religious orientation was positive. Thus, understanding how religious orientation affects malevolent creativity is vital to advancing our understanding of this area of human behavior.